A bypass mechanism of abiraterone‐resistant prostate cancer: Accumulating CYP17A1 substrates activate androgen receptor signaling. Issue 9 (24th April 2019) - Moll, Jan M.; Kumagai, Jinpei; van Royen, Martin E.; Teubel, Wilma J.; van Soest, Robert J.; French, Pim J.; Homma, Yukio; Jenster, Guido; de Wit, Ronald; van Weerden, Wytske M.
Abstract: Background: Intratumoral steroidogenesis and its potential relevance in castration‐resistant prostate cancer (CRPC) and in cytochrome P450, family 17, subfamily A, polypeptide 1 (CYP17A1)‐inhibitor treated hormone‐naïve and patients with CRPC are not well established. In this study, we tested if substrates for de novo steroidogenesis accumulating during CYP17A1 inhibition may drive cell growth in relevant preclinical models. Methods: PCa cell lines and their respective CRPC sublines were used to model CRPC in vitro. Precursor steroids pregnenolone (Preg) and progesterone (Prog) served as substrate for de novo steroid synthesis. TAK700 (orteronel), abiraterone, and small interfering RNA (siRNA) against CYP17A1 were used to block CYP17A1 enzyme activity. The antiandrogen RD162 was used to assess androgen receptor (AR) involvement. Cell growth was measured by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay. AR‐target gene expression was quantified by reverse transcription polymerase chain reaction (RT‐PCR). Nuclear import studies using cells with green fluorescent protein (GFP)‐tagged AR were performed to assess the potential of precursor steroids to directly activate AR. Results: Preg and Prog stimulated cell proliferation and AR target gene expression in VCaP, DuCaP, LNCaP, and their respective CRPC sublines. The antiandrogen RD162, but not CYP17A1 inhibition with TAK700, abiraterone or siRNA, was able to block Preg‐ and Prog‐induced proliferation. In contrast to TAK700, abiraterone also affected dihydrotestosterone‐induced cell growth, indicating direct AR binding. Furthermore, Prog‐induced AR translocation was not affected by treatment with TAK700 or abiraterone, while it was effectively blocked by the AR antagonist enzalutamide, further demonstrating the direct AR activation by Prog. Conclusion: Activation of the AR by clinically relevant levels of Preg and Prog accumulating in abiraterone‐treated patients may act as a driver for CRPC. These data provide a scientific rationale for combining CYP17A1 inhibitors with antiandrogens, particularly in patients with overexpressed or mutated‐AR.